Pemikiran Ekonomi Islam Dalam Pengelolaan Keuangan Negara Ditinjau Dari Abu Hasan Al-Mawardi - Fadhilla, Rifki Raihan (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study examines the Islamic economic thought of Abu Hasan Al-Mawardi in the context of national financial management. The research aims to analyze the concept of bait al-mal and its role in the management of national finances. The study uses a qualitative approach, analyzing the writings of Al-Mawardi and other Islamic scholars. The findings indicate that Al-Mawardi's thought emphasizes the importance of transparency and accountability in financial management, as well as the need for a balanced approach to economic development. The study concludes that Al-Mawardi's thought provides valuable insights for the development of Islamic economic thought and its application in national financial management. Keyword : Islamic Economic, Management Resources, ,management, Al-Mawardi